Neuroprotective Effects of Berry on Neurobehavioral Changes and Neuronal Loss in the Hippocampus of Mice Exposed to Acute Ionizing Radiation - Lei Guo; Qian-Qian Du; Piao-Qin Cheng; Ting-Ting Yang; Chao-Qun Xing; Xue-Zhi Luo; Xiao-Chun Peng; Feng Qian; Jiang-Rong Huang; Feng-Ru Tang (SAGE Publishing, 2022)
Background: Brain exposure to ionizing radiation during the radiotherapy of brain tumor or metastasis of peripheral cancer cells to the brain has resulted in cognitive dysfunction by reducing neurogenesis in hippocampus. The water extract of Lycium barbarum berry (Lyc), containing water-soluble Lycium barbarum polysaccharides and flavonoids, can protect the neuronal injury by reducing oxidative stress and suppressing neuroinflammation. Reseach Design: To demonstrate the long-term radioprotective effect of Lyc, we evaluated the neurobehavioral alterations and the numbers of NeuN, calbindin (CB), and parvalbumin (PV) immunopositive hippocampal neurons in BALB/c mice after acute 5.5 Gy radiation with/without oral administration of Lyc at the dosage of 10 g/kg daily for 4 weeks. Results: The results showed that Lyc could improve irradiation-induced animal weight loss, depressive behaviors, spatial memory impairment, and hippocampal neuron loss. Immunohistochemistry study demonstrated that the loss of NeuN-immunopositive neuron in the hilus of the dentate gyrus, CB-immunopositive neuron in CA1 strata radiatum, lacunosum moleculare and oriens, and PV-positive neuron in CA1 stratum pyramidum and stratum granulosum of the dentate gyrus after irradiation were significantly improved by Lyc treatment. Conclusion: The neuroprotective effect of Lyc on those hippocampal neurons may benefit the configuration of learning related neuronal networks and then improve radiation induced neurobehavioral changes such as cognitive impairment and depression. It suggests that  Lycium barbarum  berry may be an alternative food supplement to prevent radiation-induced neuron loss and neuropsychological disorders.